Execution : the discipline of getting things done - Bossidy, Larry; Charan, Ram; Burck, Charles (London : Random House, 2002)
Explains how to make the leap from the vision of a good idea to delivering results and demonstrates how to handle sudden changes in the business environment by making crucial connections among people, strategy, and the operating plan.
I: Why execution is needed -- The gap nobody knows -- The execution difference -- II: The building blocks of execution -- Building block one : the leader's seven essential behaviors -- Building block two : creating the framework for cultural change -- Building block three : the job no leader should delegate : having the right people in the right place -- III: The three core processes of execution -- The people process : making the link with strategy and operations -- The strategy process : making the link with people and operations -- How to conduct a strategy review -- The operations process : making the link with strategy and people.
Includes index.
Keywords: Management; Performance; Achievement motivation